Návrh marketingového plánu provozovny Big One Fitness - Rašovská, Aneta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2008)
Bakalářská práce pojednává o problematice marketingu v podmínkách rostoucí konkurence a stále se zvyšujících tlaků na inovační schopnosti podniků, na schopnost rychlé reakce na neustále se měnící požadavky zákazníků, na rostoucí tlaky ze strany konkurence.

This Bachelor's work is about marketing and related problems due to increasing competition and constant pressure on companies and their ability to innovate. It deals with the ability of fast reaction to constant changes of requirements from customers and increasing pressure from the competition.
Proposal of marketing plan of the Big One Fitness
Keywords: Marketingové plánování; cílový marketing; marketingový plán; jakost služeb; spokojenost zákazníka; marketingová strategie; taktické plány; marketingové cíle; segmentace trhu; marketingové prostředí; konkurence; marketingový mix; reklama a propagace; finanční plánování.; Marketing planning; target marketing; marketing plan; quality of services; satisfaction of consumer; marketing strategy; tactical plans; marketing objectives; market segmentation; marketing environment; competition; marketing mix; advertising and promotion; financial planning.